(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
There are considered possibilities to create the new concepts generalization algorithm in this paper, which would combine methods used in decision trees induction algorithm C4.5 and concepts generalization by features algorithm- CORA. The newly created algorithm will be named CORA 4.5.